2004
DOI: 10.1080/00224490409552220
|View full text |Cite
|
Sign up to set email alerts
|

Sexual‐moral attitudes, love styles, and mate selection

Abstract: Students at a southwestern university were surveyed to test the interrelations of three constructs: sexual-moral attitudes, love styles, and attraction criteria. Following the procedures of the National Health and Social Life Survey, from which the sexual-moral attitude items were obtained, we conducted a cluster analysis to create attitudinal groupings. We obtained four clusters representing various nuances of liberalism and conservatism. When compared on love styles, the clusters differed primarily on ludus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…) and good financial resources (Lacey et al . ). These traits may be valued due to the prospect of having children with a potential partner who could ‘provide’ for his family (Lacey et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and good financial resources (Lacey et al . ). These traits may be valued due to the prospect of having children with a potential partner who could ‘provide’ for his family (Lacey et al .…”
Section: Discussionmentioning
confidence: 97%
“…These traits may be valued due to the prospect of having children with a potential partner who could ‘provide’ for his family (Lacey et al . ). Women in this present research showed no interest in these qualities, implying that their expression of love could be ‘less gender stereotyped’ than it was for non‐intellectually disabled adults.…”
Section: Discussionmentioning
confidence: 97%
“…The ludus love style is associated with lower relational and sexual satisfaction (Fricker & Moore, 2002). Ludus lovers tend to engage in more infidelity (Wiederman, 1999), are more narcissistic (Campbell, Foster, & Finkel, 2002), tend to have more defeatist attitudes about romance (Williams & Schill, 1994), and possess more liberal views concerning sex, and engage in sexual interactions more frequently (Hensley, 1996;Lacey, Reifman, Scott, Harris, & Fitzpatrick, 2004). Furthermore, ludus partners perceive they are in love either very rarely or very often, depending on whether they view romantic encounters as casual affairs or love affairs (Hendrick & Hendrick, 1986).…”
Section: Love Stylesmentioning
confidence: 89%
“…For example, high openness (interest in novel experiences, aesthetics, and culture) predicts the moral virtues of emotional sensitivity (Schutte et al 1998), social tolerance (Dollinger et al 1996), political liberalism (McCrae 1996;Butler 2000), and support for universal values-the sort that would be supported by Kant's categorical imperative (Roccas et al 2002). On the other hand, low openness predicts the moral virtues of temperance, chastity, stoicism, community solidarity, pride in one's people and traditions, and clarity of gender role (manliness or femininity) (see Kendler et al 1997;Lacey et al 2004)-which academics tend to label vices ("right-wing authoritarianism," racism, sex-pg 107 # 11…”
Section: Personality Traitsmentioning
confidence: 99%